Associations of common SNPs in the SORT1, GCKR, LPL, APOA1, CETP, LDLR, APOE genes with lipid trait levels in an Algerian population sample - Meroufel, Djabaria Naïma (Int J Clin Exp Pathol, 2015)
Genome-wide association studies have identified many lipid-associated loci primarily in European and Asian populations. In view of the differences between ethnic groups in terms of the frequency and impact of these variants, our objective was to evaluate the relationships between eight lipid-associated variants (considered individually and in combination) and fasting serum triglyceride, total cholesterol, HDL- and LDL-cholesterol levels in an Algerian population sample (ISOR study, n = 751). Three SNPs (in SORT1, CETP and GCKR) were individually associated with lipid level variations. Moreover, the risk allele scores for total cholesterol, triglyceride and LDL-C levels (encompassing between three and six SNPs) were associated with their corresponding lipid traits. Our study is the first to show that some of the lipid-associated loci in European populations are associated with lipid traits in Algerians. Although our results will have to be confirmed in other North African populations, this study contributes to a better understanding of genetic susceptibility to lipid traits in Algeria.